An examination of the effectiveness of MYKE® on growth of potted American elm seedlings under greenhouse conditions - McFarlane, Liam (My University, 2018)
This thesis is an examination of the commercial mycorrhizal additive known as MYKE®, and the impact upon growth that it has on American elm seedlings grown under greenhouse conditions. Seedlings of American elm were grown in a plug tray for several months and then transferred into four-inch pots which contained various amounts of the product MYKE®. Ten pots had no product to serve as a control, ten pots had 1 gram, ten pots had 5 grams, and ten pots had 25 grams. These seedlings were grown for another three months under greenhouse conditions with regular watering. Upon being harvested, soil was carefully removed from the roots. The roots and shoots were visually inspected, photographed, and then separated at the root collar and placed into paper bags and dried at 100 degrees Celsius for three days. After drying, the stems and roots were weighed to the nearest milligram and then statistical analyses were performed on the data to see if there were statistically significant differences. The results found that there were no significant differences between the 25 gram and control in the root and shoot, and no significant differences between the 1 and 5-gram trials in the root and shoot measurements. However, there were significant differences between the two groups as illustrated by the LSD test performed. In the combined weights there were no significant differences between the control and 25 gram trials. However, the 1 gram trial was significantly different from these two in addition to the 5 gram trial. The 5 gram trial was significantly different from the control, 1 gram and the 25 gram trial. These results show that this product does work as intended and could assist in growth in an urban environment.
Keywords: American elm; MYKE®; Mycorrhizal fungi; Ulmus americana; Urban environment; Urban forestry